THE MIX MARKETING MIX FACTOR EFFECT ON PURCHASING BEHAVIOR OF ART & CULTURE MAGAZINE OF READERS IN BANGKOK - ศรีสังข์ พัฒนา (Academic Journal Phranakhon Rajabhat University, 2018)
The objectives of this research were to study readers’ purchasing behaviors of art and culture magazines in Bangkok and study mix marketing factors affecting readers’ purchasing foresaid magazines in Bangkok. This study was a survey research. Data was collected from the questionnaire. The sample of this study was 400 readers in Bangkok. Data was analyzed by using frequency, percentage, and mean. Hypotheses were tested with Chi-Square Test. The results of this study showed that the respondents mostly paid their attention to contemporary art content and have read this type of magazines for 2 - 3 years. They purchased the magazine from leading bookstore each month. They spent 1 - 2 weeks on reading. The reason to read a magazine was interesting content. They opinioned that these magazines were historical and archeological magazines which could meet their need and the magazines had value for price. The respondents mostly followed Krairit Nana, the author and kept up with news and information via art and culture related websites. In terms of marketing mix factors, all factors influenced the respondents’ purchasing behaviors of magazines. The respondents’ purchasing behaviors were influenced by product and promotion because of the highest influential level of interesting content. Purchasing channel was most influenced by price. Repurchase frequency (frequency of rereading) was most influenced by channel of distribution with a statistical significance level of .05.